Durability Assessment of Binary and Ternary Eco-Friendly Mortars with Low Cement Content - Lucas Henrique Pereira Silva; Jacqueline Roberta Tamashiro; Fabio Friol Guedes de Paiva; João Henrique da Silva Rego; Miguel Angel de la Rubia; Angela Kinoshita; Amparo Moragues Terrades (Solids, 2025)
Global cement manufacturing generated 1.6 billion metric tons of CO2 in 2022 and relies heavily on non-renewable raw materials. Utilizing agro-industrial waste as supplementary cementitious material (SCM) can help mitigate the demand for these resources. SCMs have been integrated into cement production to deliver both technical and environmental benefits to mortars and concrete. This study examines mortar blends containing blast furnace slag (BFS), Brazilian calcined clay (BCC), and bamboo leaf ash (BLA). While BFS and BCC are already established in the cement industry, recent research has highlighted BLA as a promising pozzolanic material. The SCMs were characterized, and mortars were produced to assess their flexural and compressive strength, as well as durability indicators such as electrical resistivity, chloride diffusion, migration coefficient, and carbonation resistance. The findings reveal significant performance enhancements. Partial cement replacement (20% and 40%) maintained the strength of both binary and ternary mortars, demonstrating statistical equivalence to the reference mortar (p > 0.05). It also contributed to an improved pore structure, reducing the migration coefficient by up to four times in the 20BLA20BCC mix (which replaces 20% of cement with BLA and 20% with BCC) compared to the reference mix. Chemically, the SCMs enhanced the chloride-binding capacity of the cementitious matrix by up to seven times in the case of the 20BCC mortar, thereby improving its durability. Therefore, all tested compositions—binary and ternary—showed mechanical and durability advantages over the reference while also contributing to the reduction in environmental impacts associated with the cement industry.